The book of doors eaudiobook A novel. - Brown, Gareth (HarperAudio, 2024)
A debut novel full of magic, adventure, and romance, The Book of Doors opens up a thrilling world of contemporary fantasy for readers of The Midnight Library, The Invisible Life of Addie Larue, The Night Circus, and any modern story that mixes the wonder of the unknown with just a tinge of darkness. Cassie Andrews works in a New York City bookshop, shelving books, making coffee for customers, and living an unassuming, ordinary life. Until the day one of her favorite customers—a lonely yet charming old man—dies right in front of her. Cassie is devastated. She always loved his stories, and now she has nothing to remember him by. Nothing but the last book he was reading. But this is no ordinary book... It is the Book of Doors. Inscribed with enigmatic words and mysterious drawings, it promises Cassie that any door is every door. You just need to know how to open them. Then she's approached by a gaunt stranger in a rumpled black suit with a Scottish brogue who calls himself Drummond Fox. He's a librarian who keeps watch over a unique set of rare volumes. The tome now in Cassie's possession is not the only book with great power, but it is the one most coveted by those who collect them. Now Cassie is being hunted by those few who know of the Special Books. With only her roommate Izzy to confide in, she has to decide if she will help the mysterious and haunted Drummond protect the Book of Doors—and the other books in his secret library's care—from those who will do evil. Because only Drummond knows where the unique library is and only Cassie's book can get them there. But there are those willing to kill to obtain those secrets. And a dark force—in the form of a shadowy, sadistic woman—is at the very top of that list.